Detecting sexually transmitted infections beyond the syndromic approach: lessons from a rural setting in Chiapas, Mexico - Gonzalez, Susan; Lopez Velasco, Petra Natalia; Mena Antonio, Carlos Adolfo; Palazuelos, Daniel (Frontiers in Reproductive Health, 2024)
Sexually Transmitted Infections (STIs) are a critical global health concern, with low- and middle-income countries carrying the highest burden. The development of rapid point-of-care STI tests has enabled screening in settings without laboratory access. Yet, high-need settings face unique challenges that may influence the implementation and uptake of STI screening. This piece discusses lessons learned from the implementation of STI screening in a rural, low-resource setting in Chiapas, Mexico. Despite minimal privacy and a low staff-to-patient ratio, a streamlined approach was developed to destigmatize and maximize STI screening. The clinic team developed strategies through practice, including incorporating screening into triage procedures and offering screening to family members. This protocol led to an average screening rate of 37% within three months and acceptance of screening by family units. It was observed that access to treatment was necessary to alleviate patient hesitation to screening due to fears of a positive result. As STI screening increases globally, healthcare systems must develop robust access to treatment to effectively prevent and treat STIs worldwide.